Prevalence of risk factors for bone fragility fractures among elderly residents in the municipality of Mineiros – Goiás (Research, Society and Development, 2022)
The aging process and the increase in life expectancy point to an improvement in quality of life due to its disabling events. Bone fragility fractures and their physical and psychological consequences can be avoided by recognizing the risk factors. The aim of this study was to evaluate the risk factors for fragility fractures in the elderly in the city of Mineiros/GO. An analytic-descriptive study, with cross-sectional design, was carried out, including 100 elderly assisted in health care units in Mineiros, GO. A questionnaire about incidence and risk factors for fragility fractures was carried out, determining the prevalence and risk of fractures by the FRAX-Brazil scale, the possible outcomes and the association of risk factors for fragility fractures. Thus, the prevalence of risk factors for fragility fractures was identified, and most of them were female, Caucasian, mean age 70.54 years (standard deviation 8.48), and 80% of the surveyed individuals had never undergone bone densitometry, and most of them had moderate to high risk factors for major fracture and hip fracture. We conclude that there is a need for osteoporosis prevention, early diagnosis and effective treatment, reducing the rates of these fractures. The identification of the most prevalent risk factors facilitates the implementation of short- and long-term preventive and socio-educational measures by the health service. Furthermore, it is expected to contribute to the construction of a care network for elderly patients vulnerable to falls and fragility fractures.